THE MUSICAL ACOUSTICS OF BUNDENGAN - Gea O.F. Parikesit; Indraswari Kusumaningtyas (Proceeding IICACS, 2019)
Bundengan is an Indonesian musical instrument developed by duck herders in Wonosobo, Central Java. Recently the organology of the bundengan has been studied by M. Sa’id Abdulloh from ISI Surakarta. We build upon this result and use quantitative measurements and computations to reveal the exact mechanisms of the bundengan strings (see:http://tinyurl.com/Bundengan). Our measurements show that the small bamboo clips attached to the strings is the key element on how the strings generate metallic gong-like sounds. As the string is plucked, the bamboo clips divide the string into several parts, each of them vibrating with different frequencies. This results in non-harmonic spectra, resembling the sounds from metallic instruments. Our computation show in more details how the mass of the bamboo clips determine the string vibrations. Keywords:Bundengan, acoustics, music.